Negative ion gas‐phase chemistry of arenes. Issue 1 (6th April 2015) - Danikiewicz, Witold; Zimnicka, Magdalena
Abstract : Reactions of aromatic and heteroaromatic compounds involving anions are of great importance in organic synthesis. Some of these reactions have been studied in the gas phase and are occasionally mentioned in reviews devoted to gas‐phase negative ion chemistry, but no reviews exist that collect all existing information about these reactions. This work is intended to fill this gap. In the first part of this review, methods for generating arene anions in the gas phase and studying their physicochemical properties and fragmentation reactions are presented. The main topics in this part are as follows: processes in which gas‐phase arene anions are formed, measurements and calculations of the proton affinities of arene anions, proton exchange reactions, and fragmentation processes of substituted arene anions, especially phenide ions. The second part is devoted to gas‐phase reactions of arene anions. The most important of these are reactions with electrophiles such as carbonyl compounds and α, β‐unsaturated carbonyl and related compounds (Michael acceptors). Other reactions including oxidation of arene anions and halogenophilic reactions are also presented. In the last part of the review, reactions of electrophilic arenes with nucleophiles are discussed. The best known of these is the aromatic nucleophilic substitution (SN Ar) reaction; however, other processes that lead to the substitution of a hydrogen atom in the aromatic ring are also very important. Aromatic substrates in these reactions are usually but not always nitroarenes bearing other substituents in the ring. The first step in these reactions is the formation of an anionic σ‐adduct, which, depending on the substituents in the aromatic ring and the structure of the attacking nucleophile, is either an intermediate or a transition state in the reaction path. In the present review, we attempted to collect the results of both experimental and computational studies of the aforementioned reactions conducted since the very beginning of gas‐phase negative ion chemistry. © 2015 Wiley Periodicals, Inc. Mass Spec Rev 35: 123–146, 2016.